1980
DOI: 10.1159/000117779
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme Activity of G-6-PD, γ-GT and Lysozyme in White Cells of Schizophrenics

Abstract: In a controlled study the activity of glucose-6-phosphate dehydrogenase (G-6-PD) in red and white blood cells, γ-glutamyl transpeptidase (γ-GT) and lysozyme in serum and white blood cells was studied in 22 drug-free schizophrenic patients and 17 healthy volunteers. The activities of the above enzymes were found to be reduced in the white cells of schizophrenics compared with controls. The differences in activity of G-6-PD in red cells and of γ-GT and lysozyme in serum between the two groups were not revealed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Immune abnormalities may also play a pathological role in some forms of schizophrenia [ 4 ]. In paranoid schizophrenics, but not catatonic schizophrenics, white blood cell activity is suppressed compared with that found in healthy volunteers [ 5 ]. Mittleman et al found a relative skewing of cerebrospinal fluid profiles toward type 2 cytokines and found that humoral immunity is involved in childhood-onset schizophrenia [ 6 ].…”
mentioning
confidence: 99%
“…Immune abnormalities may also play a pathological role in some forms of schizophrenia [ 4 ]. In paranoid schizophrenics, but not catatonic schizophrenics, white blood cell activity is suppressed compared with that found in healthy volunteers [ 5 ]. Mittleman et al found a relative skewing of cerebrospinal fluid profiles toward type 2 cytokines and found that humoral immunity is involved in childhood-onset schizophrenia [ 6 ].…”
mentioning
confidence: 99%